Mechanochemical conversion of chrysotile/K2HPO4 mixtures into potential sustainable and environmentally friendly slow-release fertilizers. (15th January 2018) - Borges, Roger; Baika, Loana Mara; Grassi, Marco Tadeu; Wypych, Fernando
Abstract: Chrysotile fibers pose a threat to public health due to their association relation to respiratory malignant lung disease such as cancer. For this reason, they must be stored and discarded appropriately, including after treatment, which raises costs. In the present study, insoluble chrysotile fibers were milled in solid state with highly soluble K2 HPO4, destroying both structures, making the chrysotile nontoxic and generating a new material with potential use as sustainable slow-release fertilizer (SSRF) containing mainly K and P. Based on the mills, milling conditions and chrysotile/K2 HPO4 molar ratios used, Mg originating from chrysotile fibers reacted with K and P from dibasic potassium phosphate and were transformed into MgKPO4 ·H2 O, MgKPO4 ·6H2 O and probably a mixture of amorphous SiO2 /MgO. In this study, a zirconia planetary mill and high-energy ball mill were used, both of them produced SSRF. In conclusion, it was possible to synthesize high-value and extremely useful materials for agriculture using a harmful waste. The release rate can be tailored by controlling chrysotile/K2 HPO4 molar ratios, grinding speed and time, which makes the process even more promising for farming applications. Graphical abstract: Image 1 Highlights: Chrysotile fibers were mixed with monohydrogen phosphate and milled. Several milling conditions were evaluated to destroy the chrysotile fibers. Optimizing the milling conditions, potential slow release fertilizer were obtained. The release of Mg, Si, K and P were evaluated in water for 1 and 168 h. The harmful waste can generate useful and high-value materials for agriculture.